Non-Verbal Marketing Communication Training for Teenagers of Dharma Wanita Kebonsari Special School - Zulin Nurchayati; Veny Ari Sejati; Hindun Nurhidayati (Journal of Communication, Sustainability, and Empowerment, 2026)
Teenagers with disabilities are required to be more productive in order to have a decent life and can create employment opportunities for others so that the community's life becomes more prosperous. One way is by entrepreneurship. Entrepreneurs must have marketing communication skills so that businesses can grow and develop. Therefore, marketing communication training was held for productive-age teenagers at the Dharma Wanita Special Needs School in April 2026 at the Dharma Wanita Special Needs School Kebonsari Madiun with participants who were productive-age teenagers. The results of this training were written using qualitative descriptive techniques, and data collection used interviews and participant observation where the author was directly involved daily in the implementation of the training. The purpose of writing this article explains how marketing communication training for SLB teenagers is verbally and nonverbally. Meanwhile, the purpose of holding the training is to equip productive-age SLB teenagers with marketing communication skills, how to manage a business and hopefully be able to create employment opportunities. Participants practiced making marketing plans, determining costs, creating promotions, determining places and physical evidence. It is hoped that this article will be useful for other entrepreneurs with special needs, namely increasing insight and ideas in developing their businesses.